Ответы и объяснения

Лучший Ответ!
2013-10-07T19:57:23+00:00
2.  \frac{5-3x}{25- x^{2} }  \frac{2x}{25- x^{2} }  =  \frac{5-3x+2x}{y25- x^{2} }  \frac{5-x}{25- x^{2} }  =  \frac{1}{5-x}  =  \frac{1}{5+1,5}  =  \frac{1}{6,5} = 6,5
3. a)  \frac{2x+1}{12 x^{2} y}  +  \frac{2-3y}{18xy^{2} }  \frac{18y(2x+1)}{216 x^{2}  y^{2} }  +  \frac{12x(2-3y)}{216 x^{2}  y^{2} }  =  \frac{36xy+18y}{216 x^{2}  y^{2} }  +  \frac{24x-36xy}{216 x^{2}  y^{2} }  \frac{36xy+18y+24x-36xy}{216 x^{2}  y^{2} }  \frac{18y+24x}{216 x^{2}  y^{2} }  =  \frac{6(3y+4x)}{2(108 x^{2}  y^{2}) }  =  \frac{3(3y+4x)}{36(3 x^{2}  y^{2}) } = \frac{3y+4x}{12(3 x^{2}  y^{2}) }